Decreasing Seroprevalence of Measles Antibodies after Vaccination - Possible Gap in Measles Protection in Adults in the Czech Republic - Smetana, Jan; Chlibek, Roman; Hanovcova, Irena; Sosovickova, Renata; Smetanova, Libuse; Gal, Peter; Dite, Petr (PloS one, 2017)
AIMS: In recent years, Europe has recorded an increase in the number of measles outbreaks despite the implementation of vaccination into the National Immunization Programs. The Czech Republic introduced vaccination against measles into National Immunization Program in 1969. The aim of this study was to determine seroprevalence of IgG antibodies against measles in adults. METHODS: Our study was designed as a prospective, multicenter cohort study. Samples of blood were taken from adults aged 18 years and over. Specific IgG antibodies were determined by ELISA method. RESULTS: A number of 1911 sera samples were obtained. The total seropositivity reached 83.3%, 14.3% of the results were negative and 2.4% were borderline. When comparing the individual age groups, the highest antibody seropositivity (> 96%) was detected in persons aged 50 years and over who were naturally infected in pre-vaccine era. The lowest seropositivity was recorded in the age groups 30-39 years (61.5%), 40-49 years (77.5%) and 18-29 years (81.1%). CONCLUSIONS: A long term high rate of seropositivity persists after natural measles infection. By contrast, it decreases over time after vaccination. Similarly, the concentrations of antibodies in persons with measles history persist for a longer time at a higher level than in vaccinated persons. Our results indicate possible gap in measles protection in adults born after implementation of vaccination into the National Immunization Programs. There are two probable reasons, decrease of measles antibody seropositivity in time after vaccination in setting of limited natural booster and one-dose vaccination schedule used in the first years after implementation.
Keywords: Immunoglobulin G; Male; kohortové studie; Measles; Seroepidemiologic Studies; séroepidemiologické studie; očkovací programy; Cohort Studies; Adolescent; Česká republika; Adult; hromadná vakcinace; imunoglobulin G; dospělí; Aged; mužské pohlaví; senioři; Mass Vaccination; spalničková vakcína; mladiství; Czech Republic; senioři nad 80 let; lidé; ženské pohlaví; Measles Vaccine; Humans; epidemický výskyt choroby; Immunization Programs; Aged, 80 and over; spalničky; Disease Outbreaks; Female; lidé středního věku; Middle Aged